A novel compound inhibits rHDL assembly and blocks nascent HDL biogenesis downstream of apoAI binding to ABCA1 expressing cells - Lyssenko, Nicholas N. (2011)
OBJECTIVE: Nascent high-density lipoprotein (HDL) particles form from cellular lipids and extracellular lipid-free apolipoprotein AI (apoAI) in a process mediated by ATP-binding cassette transporter A1 (ABCA1). We have sought out compounds that inhibit nascent HDL biogenesis without affecting ABCA1 activity. METHODS AND RESULTS: Reconstituted HDL (rHDL) formation and cellular cholesterol efflux assays were used to show that two compounds that bond via hydrogen with phospholipids inhibit rHDL and nascent HDL production. In rHDL formation assays, the inhibitory effect of compound 1 (methyl 3α-acetoxy-7α,12α-di[(phenylaminocarbonyl)amino]-5β-cholan-24-oate), the more active of the two, depended on its ability to associate with phospholipids. In cell assays, compound 1 suppressed ABCA1-mediated cholesterol efflux to apoAI, the 18A peptide, and taurocholate with high specificity, without affecting ABCA1-independent cellular cholesterol efflux to HDL and endocytosis of acetylated low-density lipoprotein (AcLDL) and transferrin. Furthermore, compound 1 did not affect ABCA1 activity adversely, as ABCA1-mediated shedding of microparticles proceeded unabated and apoAI binding to ABCA1-expressing cells increased in its presence. CONCLUSIONS: The inhibitory effects of compound 1 support a three-step model of nascent HDL biogenesis: plasma membrane remodeling by ABCA1, apoAI binding to ABCA1, and lipoprotein particle assembly. The compound inhibits the final step, causing accumulation of apoAI in ABCA1-expressing cells.